Ceftiofur-resistant Salmonella enterica serovar Heidelberg of poultry origin – a risk profile using the Codex framework. (2019) - Carson, Carolee; Li, Xian-Zhi; Agunos, Agnes; Loest, Daleen; Chapman, Brennan; Finley, Rita; Mehrotra, Manisha; Sherk, Lauren M.; Gaumond, Réjean; Irwin, Rebecca
Abstract: Codex published the 'Guidelines for Risk Analysis of Foodborne Antimicrobial Resistance' to standardise the approach for evaluating risk posed by foodborne antimicrobial-resistant bacteria. One of the first steps in the guidelines is to compile a risk profile, which provides the current state of knowledge regarding a food safety issue, describes risk management options and recommends next steps. In Canada, ceftiofur/ceftriaxone-resistant Salmonella enterica subsp. enterica serovar Heidelberg from poultry was identified as an antimicrobial resistance (AMR) food safety issue. The first objective of this article was to contextualise this food safety issue, using the risk profile format of the Codex Guidelines. A second objective was to evaluate the applicability of the Codex Guidelines. This risk profile indicated that ceftiofur/ceftriaxone-resistant S . Heidelberg (CSH) was commonly isolated from poultry and was associated with severe disease in humans. Ceftiofur use in poultry hatcheries temporally mirrored the prevalence of CSH from poultry meat at retail and from people with salmonellosis. The evidence was sufficient to indicate the need for risk management options, such as restricting the use of ceftiofur in poultry. The Codex Guidelines provided a useful approach to summarise data for decision-makers to evaluate an AMR food safety issue.